Primary non-response in inflammatory arthritis treated with biologics and targeted therapies in daily clinical practice - Leticia Leon; Dalifer Freites-Nuñez; Esther Toledano; Gloria Candelas; Cristina Martinez; María Rodríguez-Laguna; Benjamín Fernández-Gutiérrez; Lydia Abasolo (Therapeutic Advances in Musculoskeletal Disease)
Background: Switching between therapies is a recommended strategy for rheumatoid arthritis (RA) and psoriatic arthritis (PsA) patients who experience treatment failure; moreover, data on switching due to primary non-response and subsequent failures are limited. Objectives: To obtain information from clinical practice regarding failures due to primary non-response in patients on biologic and target synthetic disease-modifying antirheumatic drugs (ts/bDMARDs), assessing the incidence rate (IR) of switching due to primary non-response and risk of subsequent treatment failure by cycling compared to swapping. Design: A longitudinal retrospective study, spanning from 2007 to 2022, was conducted on patients with RA or PsA treated with ts/bDMARDs at an outpatient rheumatology clinic. Methods: The main outcomes were as follows: (1) ts/bDMARD failure due to primary non-response and (2) subsequent discontinuation of prescribed ts/bDMARD due to lack of efficacy. The independent variable was switching between classes compared to switching within class. As covariates, clinical, sociodemographic, clinical, and treatments were considered. To estimate ts/bDMARDs switching rates, survival techniques were used, expressing the IR per 100 patients * year with their 95% confidence interval. Cox multivariate regression analyses were run to assess the role of switching between/within class in the subsequent treatment failure. Results: In total, 327 patients were included. Of these, 50 patients in 77 treatment courses developed primary non-response with an IR of 4.25 (3.4–5.3). The IR was quite similar between RA and PsA, higher in women, and in those who started ts/bDMARDs after 2018. In those with primary non-response, there were 42 subsequent treatment failures with an IR of 26.38 (19.49–35.69). The multivariate model showed that cycling increased the risk of subsequent failure compared to swapping (hazard ratio: 2 (1.1–3.77), p  = 0.03). Conclusion: This study provides support to consider swapping a better alternative rather than cycling after primary non-response.